Onychomycosis unresponsive to antifungals: Etiology and treatment with a new direct technique - Fatma Gülru Erdogan; Dilsun Yıldırım; Gül Aslıhan Çakır Akay (Wolters Kluwer Medknow Publications, 2019)
Aims and Objectives: The aim of this study was to identify the fungal agents causing onychomycosis that were unresponsive to antifungal treatment and to treat these cases by placing under-nail cushions with a mild keratolytic to clear the fungus-invaded tissue. Materials and Methods: Fungal agents were identified by the matrix-assisted laser desorption/ionization time of flight (MALDI-TOF) technique. Results: Nine patients had Aspergillus spp. (7 Aspergillus niger,2 Aspergillus flavus); four had Candida species and one had Trichophyton rubrum. All patients were free of infection at the end of treatment. Conclusion: As per the results, we may state that onychomycosis that is unresponsive to treatment in immunocompetent patients seems to be mostly associated with molds. Direct application of a mild keratolytic to the fungus-invaded part, e.g., the nail plate and/or nail bed and removal of fungal elements may provide a successful treatment outcome.